2012
DOI: 10.4329/wjr.v4.i12.462
|View full text |Cite
|
Sign up to set email alerts
|

Potential of18F-FDG-PET as a valuable adjunct to clinical and response assessment in rheumatoid arthritis and seronegative spondyloarthropathies

Abstract: AIM:To evaluate the role of fluorine-18-labeled fluorodeoxyglucose positron emission tomography ( 18

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 12 publications
2
31
0
1
Order By: Relevance
“…18 F-FDG, a glucose analog, is the most common tracer; it is taken in by metabolically active cells, such as neoplastic cells. According to recent studies, 18 F-FDG PET sensitively detects active inflammation in rheumatic diseases, including synovitis in RA [12][13][14][15][16][17][18]. In contrast, 18 F-NaF PET is an increasingly used molecular imaging modality in human skeletal disorders [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 95%
“…18 F-FDG, a glucose analog, is the most common tracer; it is taken in by metabolically active cells, such as neoplastic cells. According to recent studies, 18 F-FDG PET sensitively detects active inflammation in rheumatic diseases, including synovitis in RA [12][13][14][15][16][17][18]. In contrast, 18 F-NaF PET is an increasingly used molecular imaging modality in human skeletal disorders [19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 95%
“…As a modality for the diagnosis of sacroiliitis, [ 18 F]FDG PET/CT has been shown to be of little value, with negative results in all 10 patients with ankylosing spondylitis (AS) in one study,13 showing inconsistent results in another,14 and assessed as not useful for predicting response to TNF-alpha antagonist therapy in a third study 15. However, [ 18 F]fluoride, which is a bone tracer of osteoblastic activity, was found useful for demonstrating bone activity in AS patients 13.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, there are reports suggesting an absence of association between symptoms and foci of increased uptake at the acetabular fossa [18], the knees and lumbar interspinous ligaments in patients with polymyalgia rheumatica [19, 20] atlantoaxial joints of patients with rheumatoid arthritis [12], and knees in patients with osteoarthritis [21]. However, the data is far from clear on this point, and other investigators have found significant differences in FDG avidity of symptomatic knees and shoulders when compared to that of asymptomatic joints [22, 23], and association of increased uptake at painful joints in patients with rheumatoid arthritis [24, 25]. Further study is needed to better define the role of 18 F-FDG PET in detection of common musculoskeletal conditions.…”
Section: Discussionmentioning
confidence: 99%